The Effect of Virtual Blended Learning Models with PhET Assistance on Students' Mastery of Concepts in Fluid Material - Mei Kurniadi; Supriyono Koes Handayanto; Sutopo Sutopo (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of blended learning virtual learning models on PhET-assisted fluid material on students' conceptual comprehension. The design model used in this research is an experiment with a pretest-posttest type. The sample used in this study was Class XI IPA C as the experimental object consisting of 35 students in one class. The test given was in the form of a concept comprehension ability test consisting of 10 multiple choice questions with a maximum score of 100. The results showed that the average posttest score was higher than the average pretest score in the experimental class. In addition, an N-gain value of 0.62 was obtained, which means that the value of increasing student learning outcomes using the phet-assisted virtual blended learning model is in the medium category. This shows that the use of PhET-assisted blended learning virtual models has an effect on students' mastery of concepts.